Alcohol and Suicide in Eastern Europe - Y E Razvodovsky (Journal of Addiction Medicine and Therapeutic Science - Peertechz Publications, 2015)
Suicide is one of the leading external causes of death in many countries and it burden is expected to be rising [1]. There are a number of possible reasons responsible for this including lessened social integration, increase in psychiatric disorders, alcohol and drug abuse [2,3]. Alcohol consumption and suicides rates in Eastern Europe (EE) are among the highest in the world [4]. In a number of studies using various designs alcohol consumption has been found to be important risk factors of suicide in EE [5-7]. The empirical literature provides evidence of an association between alcohol and suicide at the individual level in many EE nations [8]. Most of the evidence linking excessive drinking and suicide in EE is based on population data. Both longitudinal and cross-sectional aggregate level studies usually report a significant and positive association between alcohol consumption and suicide [5,6,9].